Pengaruh Harga Dan Ulasan Pelanggan Online Terhadap Keputusan Pembelian Produk Hijab Bella Square Di Shopee - Showaba, Nathiqoh; Chrismardani, Yustina (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This research examines the influence of price and online customer reviews on purchasing decisions for Bella Square hijab products at Shopee. With quantitative research methods using SPSS 25 analysis and purportive sampling techniques. Respondents consisted of 97 female students from the Faculty of Economics and Business, Trunojoyo University, Madura. The research results show that prices and online customer reviews partially and simultaneously have a significant influence on purchasing decisions for Bella Square Hijab products at Shopee with a significance value of less than 0.05.